Membangun Kesadaran Pengelolaan Keuangan Rumah Tangga Melalui Edukasi Financial di Desa Pattallikang Kecamatan Manuju, Kabupaten Gowa - Mustari; Nurjannah; Andi Izzatul Fiddah; Nur Arisah; Andi Muchlis Sirajuddin; Nahriana (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2023)
Servants have a strategic role as agents of change. Servants directly engage in community service through the provision of training assistance, counseling, guidance, mentoring and to awaken their potential, and help improve the quality of life and development. Servants will get generative abilities in the form of life skills (life skills). Observations were carried out using the following methods: (1) Gathering, (2) Documentation, and (3) seeing the field directly. Based on the results of observations carried out in Pattallikang Village by looking at the potential of the community and supporting environmental conditions. The work programs carried out are Social Service (Social Service), outreach, hospitality to the people of Pattallikang Village, Building Awareness of Household Financial Management through Financial Education, and introducing the BUMENRA Book to villagers, and Social Service in the Campus Area.